Kualitas Fungsional dan Kepuasan Pasien terhadap Perawat dan Dokter Gigi di Rumah Sakit - Afifa Nur Chabibah (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: The quality of healthcare is an important aspect to be implemented by hospitals as a healthcare facility. Doctors and nurses are human resources that directly provide services to patients. Interpersonal communication between physicians and nurses with patients may influence patients’ satisfaction as an output of service quality.Aim: This study aimed to identify the functional quality of nurses and dentists on patients’ satisfaction at Dental Polyclinic of Dr. R. Sosodoro Djatikoesoemo Bojonegoro Hospital.Method: This research was a quantitative descriptive and observational research. The data were gathered from 68 respondents. Primary data were collected through a questionnaire disseminated for patients at Dental Polyclinic from 14th to 26th of May 2018. The data were processed and analyzed by using 2x2 position matrix.Results: The results show that the functional quality of nurses is in quadrant IV (3.18; 3.21), and functional quality of doctors is in quadrant II (3.48; 3.46).Conclusion: This study concludes the nurses’ functional quality still must be improved and promoted to the patients regarding to their competence, assurance (3S application and nurse's hospitality), and empathy (nurses’ tranquility) while overall dentists’ functional quality (competence, assurance, and empahty) is maximized.Keywords: dentists, functional quality, hospital, nurses, satisfaction